Metabolic factors associated with the diagnosis of preeclampsia in pregnant women of Sergio E. Bernales hospital, from january to december of the year 2018 - Castañeda-Campos, José Luis (2019)
Objective: To establish the existing association between presenting metabolic factors and to present preeclampsia in pregnant women, in the National Hospital Sergio E. Bernales during January - December of the year 2018. Methods: An analytical, correlational, observational, retrospective and retrospective study of cases and controls was performed on 480 pregnant women who were treated in the Gyneco-Obstetrics Service of the Sergio E. Bernales National Hospital during the period January - December 2018. Cases and controls were randomly selected, 137 pregnant women with the diagnosis of preeclampsia and 243 pregnant patients without the diagnosis of preeclampsia. The information was obtained from the clinical histories, through data collection sheets, these were processed in the statistical program SPSS v.25. In order to establish the association between the categorical variables, the chi-square test was used, with a confidence level of 0.05; in addition, the crude Odds Ratios (OR) were determined in a 95% confidence interval. To eliminate the confounding variables, the adjusted Odds Ratios were determined. Results: Of the pregnant patients with preeclampsia, 59.1% did not present severe characteristics, while 40.9% did present severe characteristics. The metabolic factors in which an association with preeclampsia was found were gestational diabetes (P = 0.005, OR = 3.744, CI = 1.487-9.423), BMI ≥25kg / m2 at the beginning of pregnancy (P = 0.006, OR = 2.019, IC = 1.220-3.340) and pregestational diabetes (P = 0.022, OR = 4.304, CI = 1.238-14.966); There was also an association with other factors associated with preeclampsia, such as a history of preeclampsia (P = 0.007, OR = 3.027, CI = 1.346-6.809), history of HTA (P = 0.019, OR = 3.394, CI = 1.222-9.422) and history of family with HTA (P = 0.000, OR = 6.062, CI = 2.470-14.876); no association was found in the multivariate analysis with the pregnant variable aged (P = 0.140) despite the fact that if there was an association in the bivariate analysis, it is taken as a confounding variable. Conclusions: The metabolic factors in which an association with preeclampsia was found in the Sergio E. Bernales Hospital in 2018 were having gestational diabetes, a BMI at the beginning of pregnancy greater than or equal to 25kg / m2 and pre-gestational diabetes